Doses de fósforo associadas ao nitrogênio no desenvolvimento de mudas de cafeeiro - Santinato, Felipe; Caione, Gustavo; Tavares, Tiago Oliveira [UNESP]; Prado, Renato de Mello [UNESP] (My University, 2014)
A greater supply of nitrogen in the substrate using organic compost for coffee (Coffea arabica L.) seedlings can increase the effects of phosphorus in the plant and thereby promoting growth of biomass, enhancing the growth of plants when they are transplanted into the growing environment. The objective was evaluate the effect of phosphorus levels higher than those usually recommended in the absence and presence of nitrogen supplementation in the preparation of substrate containing organic compound to produce coffee seedlings grown in bags. The experiment was installed at a nursery in Araxá city, Minas Gerais State, Brazil in may 2011, using substrate containing 70 % of soil samples and 30% of cattle manure, with the addition of 1 kg m-3 of potassium chloride and 1 kg m-3 of dolomitic lime. We used coffee seedlings of Catuaí Vermelho cultivar IAC 144 grown in polyethylene bags (1694 cm3). The experiment was installed in a completely randomized design with four replicates and 12 treatments in a 6 × 2 factorial scheme, with six levels of phosphorus (P): 0, 109, 218, 436, 872 and 1308 mg dm-3, as triple superphosphate; and two levels of nitrogen (N): absence and 100 mg dm-3 in the form of urea. The biometric variables, seedlings quality indexes, soil P concentration as well as accumulation of N and P by plants were determined at 180 days after sowing. Through regression analysis to conclude that the application of phosphorus in the substrate enhanced the P concentration in soil and plant, reflecting in the growth and dry matter production of coffee seedlings, especially in the presence of nitrogen. The highest tested dose of phosphorus (1308 mg dm-3) is the most appropriate dose for the production of coffee seedlings. The addition of nitrogen to the substrate containing cattle manure is important to supply the need of this nutrient in the seedlings.
Doses of phosphorus associated with nitrogen on development of coffee seedlings
Keywords: Coffea arabica L.; Dickson index; Phosphorus fertilization; Seedling quality